Agamben, Giorgio, Autorretrato en el estudio, (trad. de Rodrigo Molina-Zavalía y María Teresa D´Meza), Buenos Aires, Adriana Hidalgo, 2018, 140 pp. - Litvinoff, Diego Ezequiel (Anales del Seminario de Historia de la Filosofía, 2019)
La libreta como forma-de-vida. Sobre Autorretrato en el estudio de Giorgio Agamben